2018
DOI: 10.1111/1346-8138.14517
|View full text |Cite
|
Sign up to set email alerts
|

Prolonged growth of infantile hemangioma after pulsed dye laser and oral propranolol treatment

Abstract: Infantile hemangiomas are the most common tumor of childhood and undergo rapid growth during early infancy followed by gradual involution. After involution, residual lesions sometimes remain. Oral propranolol usually induces earlier involution and redness reduction of infantile hemangiomas. However, the optimal treatment duration is unknown and infantile hemangiomas sometimes recur after cessation of treatment. We report three Japanese patients with recurrent infantile hemangiomas on their cheek. These patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…Because of the lack of further examinations, there was no direct evidence to definitively determine whether propranolol withdrawal or nebulized salbutamol therapy caused the deterioration in this case. Current reports of IH deterioration after propranolol discontinuation or β2-AR agonist administration suggested that it was not a common occurrence and the interval time varied widely from 1 to 8 months ( 12 , 26 ). A variety of factors can play a role in IH deterioration, and the exact mechanism remains unclear.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because of the lack of further examinations, there was no direct evidence to definitively determine whether propranolol withdrawal or nebulized salbutamol therapy caused the deterioration in this case. Current reports of IH deterioration after propranolol discontinuation or β2-AR agonist administration suggested that it was not a common occurrence and the interval time varied widely from 1 to 8 months ( 12 , 26 ). A variety of factors can play a role in IH deterioration, and the exact mechanism remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Shinji et al. ( 26 ) reported three cases of IH rebound in 1 month after completing the treatments, in multiple times. Nicole et al.…”
Section: Discussionmentioning
confidence: 99%
“…Ultrasound is helpful in assessing treatment efficacy upon termination by measuring IH thickness and vascularity [ 46 ]. Patients with IH who received oral propranolol should be followed up to at least 6 months [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…Ultrasound is helpful in assessing treatment efficacy upon termination by measuring IH thickness and vascularity [46]. Patients with IH who received oral propranolol should be followed up to at least 6 months [47]. Topical beta-blockers have been proven to be efficacious and safe in treating PG as well, mostly for small, superficial infantile PG and PG-like lesions induced by EGFR-I [22].…”
Section: Mild Dizziness and Gi Discomfortmentioning
confidence: 99%
“…The known risk factors of IH recurrence are female sex, tumor size over 50 cm 3 , tumor location on head and neck, deep or mixed type hemangioma, and early treatment withdrawal (<9 months) [37]. Kagami et al suggest that patients with IH should be monitored for up to 6 months after the cessation of treatment [38]. In a follow-up study of the outcomes of propranolol treatment, in a group of 80 patients, lesions were found in 91.2% (73/80).…”
Section: Recurrence and Residual Lesions After Propranolol Treatmentmentioning
confidence: 99%